Low Energy Precipitating Electrons in the Diffuse Aurorae. Issue 7 (3rd April 2019) - Wing, Simon; Khazanov, George V.; Sibeck, Dave G.; Zesta, Eftyhia
Abstract: Auroral electron precipitation is often classified into three categories: diffuse, monoenergetic, and broadband. However, some precipitating electrons do not fit any of the three categories, which are assumed to be "diffuse" electrons for convenience. Many of these nonconforming electrons exhibit high fluxes at low energies. Most studies assume that the precipitating electrons originate from the magnetosphere. However, this primary precipitation is only the first step in the formation of the electron precipitation. The primary precipitation creates secondary electrons and both electron populations bounce many times between the conjugate points. Thus, the full electron precipitation consists of not only the primary but the Multiply Reflected Primary and Secondary (MRPS) electrons. The MRPS electrons are modeled with Superthermal Electron Transport model. The model‐data comparisons suggest that the low energy electrons in the nonconforming precipitating electrons can be attributed to MRPS electrons. Key Points: The complete picture of electron precipitation consists of not just the primary electrons but also the secondary electrons The secondary electrons can explain the low energy component of the nonconforming electron precipitation that shows high fluxes The STET simulations of multiply reflected primary and secondary electrons compare well with DMSP observations